1990
DOI: 10.1128/aac.34.7.1422
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of amikacin in serum and in tissue contiguous with pressure sores in humans with spinal cord injury

Abstract: Pressure sores are a common occurrence in immobilized patients. They increase morbidity and mortality and impede rehabilitation. Antibiotics are routinely used to assist in effecting a cure when infection is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Segal et al 67 found that the elimination half-life of amikacin in IF was far longer than the calculated serum half-life of amikacin in patients with SCI. This phenomenon could not have been predicted from conventional PK models, which usually do not incorporate antibiotic levels measured directly in infected tissue fluids.…”
Section: Eliminationmentioning
confidence: 98%
See 1 more Smart Citation
“…Segal et al 67 found that the elimination half-life of amikacin in IF was far longer than the calculated serum half-life of amikacin in patients with SCI. This phenomenon could not have been predicted from conventional PK models, which usually do not incorporate antibiotic levels measured directly in infected tissue fluids.…”
Section: Eliminationmentioning
confidence: 98%
“…Assigning levels of probability to the likelihood of accuracy of each of the several decision-making factors enables us to arrive at an aggregate estimate of decision quality. 77 Mean population PK parameters generated by research into the clinical pharmacology of SCI, 50,67,74,78 serum-drug concentrations measured in individual patients, and descriptive/demographic data can be used in a Bayesian analysis. Maximum a priori information derived from the SCI population can be incorporated into the Bayesian algorithm along with individual serum levels to improve the accuracy of predicting serum concentrations and estimating individual PK parameters.…”
Section: The Relevance Of Population-specific Pk/pd Modelingmentioning
confidence: 99%
“…Patients with SCI experience characteristic diverse physiologic and metabolic disorders. Profound muscle wasting, an increase in body fat relative to lean body mass, a postinjury catabolic state associated with obligatory negative nitrogen balance, anemia, 87 susceptibility to pressure ulcers, 88 osteomyelitis, poor wound healing, 28,89 carbohydrate intolerance, dyslipidemias, 21 and impaired gastrointestinal motility or drug absorption are among the myriad comorbidities and pathobiologic sequelae that follow SCI. 54 Welldefined links between the organ systems involved in these metabolic disorders, central sympathetic and adrenergic failure, disorders of immunomodulation, 63,74,75,90,91 and altered local and systemic turnover or activation of cytokines and adhesion molecules are readily demonstrable by quantitative techniques such as flow cytometry.…”
Section: Biotransformation and Metabolism Of Drugsmentioning
confidence: 99%